Improving Narrative Essay Writing Skills Through the Use of the Classroom Reading Program Method for Class V Students at SDN 1 Nunggi - Syafruddin, Syafruddin (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The aim of this research is: to determine the increase in learning outcomes in the ability to write narrative essays using the student class reading program method. The target of the activity was 26 class students at SDN 1 Nunggi, the activity was carried out by researchers and Indonesian language teachers and the school principal helped with its implementation. Information is collected through observation, inspection and documentation. Research materials were analyzed using quantitative and qualitative data analysis. The results of the research show that the classroom reading program method can improve the narrative essay writing skills of fifth grade students at SDN 1 Nunggi. The results of the evaluation of narrative essay writing skills show the average words achieved by students in the initial situation, namely. 56.42, while the average for cycle I was 65.6, which is an increase compared to the initial state of 9.18. In the second fall, the average student score was 71.9, i.e. increased by 6.3 compared to the average score of cycle I tests. The proportion of those who reached the completion criteria also increased, i.e. in the initial state it was 31% in the first cycle. 62% or experienced an increase in fullness criteria by 31% at the beginning and Cycle II reached 88% or an increase of 26% compared to Cycle I